Ab Initio High-Pressure Study of Semiconductor-Metal Phase Transition of the Chalcogenide Compound KPSe6 - P. O. Jomo; C. O. Otieno; P. W. O. Nyawere (Advances in Condensed Matter Physics)
We report the results of pressure-induced semiconductor-metal phase transition of the semiconducting chalcogenide compound KPSe6 under high pressure using the ab initio methods. The ground-state energy calculations were performed within density functional theory and the generalized gradient approximation using the pseudopotential method with plane-wave basis sets. The projector augmented-wave (PAW) pseudopotentials were used in our calculation. The optimized lattice parameters were found from total energy calculations as 13 Bohr, 1.6 Bohr, and 1.8 Bohr for cell dimensions one, two, and three, respectively, which are in good agreement with experimental calculations. At zero pressure, the material portrayed a semiconducting property with a direct bandgap of ≈1.7 eV. As we subjected the material to pressure, the band gap was observed to reduce until it disappeared. The phase transition from the semiconductor to metal was found to occur at ∼45 GPa, implying that the material underwent metallization as pressure was increased further.